Optimal wave energy extraction for oscillating water columns using second-order sliding mode control - Mosquera, Facundo (2020)
Ocean waves are an important renewable energy resource and several fields of R&D are concurrently working to improve technologies for harnessing their power. In that context, this study presents a control to optimise the performance of oscillating water column systems. As a first contribution, a novel criterion to attain maximum wave energy extraction is developed, resulting in an enhancement of the global power efficiency of the system. Then, taking advantage of the proposed criterion, a second-order sliding mode control set-up is designed, with power extraction maximisation the primary objective and reactive power regulation a secondary one. Simulation results confirm the highly satisfactory performance of the proposed controller and its robustness in the presence of the inherent uncertainties and disturbances in the non-linear system.